Creation of the world in works of certain contemporary Lithuanian and Polish poets: from socrealism till present - Peluritytė-Tikuišienė, Audinga (Literatūra, 2016)
During the decades of the first independence, Lithuanian poetry has followed the European tradition of modernism.The best Lithuanian poetry represented authentic European modernism, its stylistic diversity and individualism. Nevertheless, the Soviet reality limited Lithuanian literature to a particularly hermetic world that protractedly ignored the experience of European art; it exalted socialist realism and its collectiveness, as well as impersonality.Lithuanian social-realist poetry has essentially encroached on the historical memory of town and culture as well as Christian metaphysics. Without metaphysics, contemporary Lithuanian poetry has faced the physical and utopian time line of Communism, propagated by the dogmas of socialist realism. Talented Lithuanian poets didn’t consider that such a possibility can be creative.During the Soviet era Lithuanian literature had been looking for its ontological identity in the prehistory of Baltic culture, international mythology of the earth ethos and the non-historical space of the Orient, which during the decades of the second independence were anchored already as a tradition of Lithuanian poetry.Meanwhile, in Polish literature, even during the period of socialist realism, they were able to stay in Christian discourse, and this was due to a stronger tradition of modernism, which allowed to carry out complex and more purposeful experiments of poetic form.When independence was restored, similar tendencies became significant: young Polish and Lithuanian writers adored some Polish poetry classics (mostly the neo-classics: Cz. Miłosz, Szymborska and Herbert) and were able to retain if not the attitude of Christian metaphysics then at least that of Christian ethics, as well as the philosophical and moral authority of Christianity under the circumstances of Soviet censorship.Towns and the history of human culture have become the mark of the world-view of contemporary Polish neo-classicism. Nobel prizes provided those marks with important international recognition. The civic attitude of Cz. Miłosz, as well as poetic philosophy in emigration writings, facing the regained independence of Poland have become an important moral argument for the expansion of the neo-classicist school in Poland. The excellence of Szymborska’s and Herbert’s poetry and philosophical attitude created a pretext of prosperity for the neo-classicist tradition in Polish poetry.